Influencia de la carga instantánea en los indicadores de producción de leche (UDIV) del hato bovino pasto y forraje ESPAM MFL - Cedeño Vera, Mayra Lourdes (2017)
ABSTRACT In the present research, the following variables were evaluated: botany composition (%), grass height (cm), structural quality (kg), milk production (kg), milk composition in (%) were evaluated. These variables were measured every 30 days, 21 dairy cows were used, and a completely random block design was applied, rotating in different extensions of land used with the treatments (T1: 20.25 ha), (T2: 0.40 ha) And (T3: 0.55 ha). The statistical package “Infostat” 2013 was used for the analysis of variance test. The results showed that the botanical composition obtained the best values in T1: Savoy: 35.95%; Star: 36.95%; Desmodium: 15.47%; Shenna 12.07%; Tree: 1.43% and broadleaf 1.98%. The highest grass height for T2 (T2: 0.40 ha); Was Savoy 100 cm; and for treatment one (T1: 0.25 ha): Star 46 cm. The structural quality for the treatment two (T2: 0.40 ha.) with the green grass 1742.25 kg / biannual and the dry grass 409.75 kg / biannual. Milk production (T2: 0.40 ha) with 6.07 kg / milk / cow / day was the highest, while the lowest production was the treatment (T3: 0.55 ha) with 3, 98 kg / milk / cow / day. In the milk composition treatment one (T1: 0.25 ha) with 13.49% for total solids, 3.9% to fats and 2.92% to proteins. It was concluded that the instantaneous load influenced the production indicators such as, grass height, structural quality and milk production, since there were significant differences, while for the botanical composition and milk composition there were no significant differences.